2016
DOI: 10.1095/biolreprod.115.137661
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ubiquitin Ligase CRL4 Regulates Proliferation and Progression Through Meiosis in Chinese Mitten Crab Eriocheir sinensis1

Abstract: The Cullin-RING E3s are multisubunit ubiquitin ligases composed of a scaffold protein known as Cullin, a RING finger protein that regulates diverse cellular pathways; however, their contribution to male gonad development, especially the spermatogenesis of the Chinese mitten crab (Eriocheir sinensis), is not well understood. We identified five evolutionarily conserved Cullins from the transcriptome and genome ofE. sinensis that are potentially involved in regulating male gonad development. The aim of the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…In mammals, the role of p53 in testis is to modulate DNA repair and cell apoptosis to control quality and quantity of mature spermatozoa during spermatogenesis [ 32 ]. Studies found that p53 homeostasis was maintained by the E3 ubiquitin ligase Cul4 complex in primary spermatocytes to maintain male fertility, as p53 could induce cell cycle arrest to allow DNA meiotic reshuffling and correction of DNA damage [ 33 ]. The cell cycle gene p53 also played a critical role in the maintenance of undifferentiated state by inhibiting a mammalian target of the rapamycin complex 1 (mTORC1) in spermatogonia [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, the role of p53 in testis is to modulate DNA repair and cell apoptosis to control quality and quantity of mature spermatozoa during spermatogenesis [ 32 ]. Studies found that p53 homeostasis was maintained by the E3 ubiquitin ligase Cul4 complex in primary spermatocytes to maintain male fertility, as p53 could induce cell cycle arrest to allow DNA meiotic reshuffling and correction of DNA damage [ 33 ]. The cell cycle gene p53 also played a critical role in the maintenance of undifferentiated state by inhibiting a mammalian target of the rapamycin complex 1 (mTORC1) in spermatogonia [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, p53 is an active participant in DNA repair and DNA damage response pathways [ 32 ]. In E. sinensis testis, p53 was also found to mediate spontaneous germ cell apoptosis to eliminate defective germ cells [ 33 ]. What's more, the mitochondria-dependent apoptotic pathway involving caspase 3 and caspase 9 was initiated.…”
Section: Introductionmentioning
confidence: 99%
“…To check the accuracy of the predicted gene model, we designed primers to re-clone the full-length cDNA. The gene organization (intron/exon boundaries) was predicted using Genscan software (http://genes.mit.edu/GENSCAN.html) (Burge and Karlin, 1997) and the schematic diagram of the Es-DBB1 gene organization was constructed according to the predicted results (Wang et al, 2016).…”
Section: Structural Characterization Of the Ddb1 Genementioning
confidence: 99%